Optical cycling of AlF molecules. (29th June 2021) - Hofsäss, S; Doppelbauer, M; Wright, S C; Kray, S; Sartakov, B G; Pérez-Ríos, J; Meijer, G; Truppe, S
Abstract: Aluminium monofluoride (AlF) is a promising candidate for laser cooling and trapping at high densities. We show efficient production of AlF in a bright, pulsed cryogenic buffer gas beam, and demonstrate rapid optical cycling on the Q rotational lines of the A 1 Π ↔ X 1 Σ + transition. We measure the brightness of the molecular beam to be >10 12 molecules per steradian per pulse in a single rotational state and present a new method to determine its velocity distribution in a single shot. The photon scattering rate of the optical cycling scheme is measured using three different methods, and is compared to theoretical predictions of the optical Bloch equations and a simplified rate equation model. Despite the large number of Zeeman sublevels (up to 216 for the Q(4) transition) involved, a high scattering rate of at least 17(2) × 10 6 s −1 can be sustained using a single, fixed-frequency laser without the need to modulate the polarisation. We deflect the molecu-lar beam using the radiation pressure force and measure an acceleration of 8.7(1.5) × 10 5 m s −2 . Losses from the optical cycle due to vibrational branching to X 1 Σ +, v ″ = 1 are addressed efficiently with a single repump laser. Further, we investigate two other loss channels, parity mixing by stray electric fields and photo-ionisation. The upper bounds for these effects are sufficiently low to allow loading into a magneto‐optical trap.